Triol-promoted activation of C–F bonds: Amination of benzylic fluorides under highly concentrated conditions mediated by 1,1,1-tris(hydroxymethyl)propane - Champagne, Pier Alexandre; Saint-Martin, Alexandre; Drouin, Mélina; Paquin, Jean-François (Beilstein Journal of Organic Chemistry, 2013)
Activation of the C–F bond of benzylic fluorides was achieved using 1,1,1-tris(hydroxymethyl)propane (2) as a hydrogen bond-donating agent. Investigations demonstrated that hydrogen bond-donating solvents are promoting the activation and hydrogen bond-accepting ones are hindering it. However, the reaction is best run under highly concentrated conditions, where solvents cannot interfere with the interaction between the organofluorine compound and the triol. Various benzylic fluorides react with secondary amines or anilines to form benzylic amines in good yields.
Keywords: C–F bond activation; highly concentrated conditions; nucleophilic substitution; hydrogen bond; organofluorine; triol

(untitled) - Amii, H.; Uneyama, K. (Chem. Rev., 2009)

(untitled) - Ahrens, M.; Scholz, G.; Braun, T.; Kemnitz, E. (Angew. Chem., Int. Ed., 2013)

(untitled) - Janjetovic, M.; Träff, A. M.; Ankner, T.; Wettergren, J.; Hilmersson, G. (Chem. Commun., 2013)

(untitled) - Azhakar, R.; Roesky, H. W.; Wolf, H.; Stalke, D. (Chem. Commun., 2013)

(untitled) - Haufe, G.; Suzuki, S.; Yasui, H.; Terada, C.; Kitayama, T.; Shiro, M.; Shibata, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Caputo, C. B.; Stephan, D. W. (Organometallics, 2012)

(untitled) - Douvris, C.; Nagaraja, C. M.; Chen, C.-H.; Foxman, B. M.; Ozerov, O. V. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, L.; Zhang, W.; Liu, J.; Hu, J. (J. Org. Chem., 2009)

(untitled) - Matsubara, K.; Ishibashi, T.; Koga, Y. (Org. Lett., 2009)

(untitled) - Blessley, G.; Holden, P.; Walker, M.; Brown, J. M.; Gouverneur, V. (Org. Lett., 2012)

(untitled) - Choi, J.; Wang, D. Y.; Kundu, S.; Choliy, Y.; Emge, T. J.; Krogh-Jespersen, K.; Goldman, A. S. (Science, 2011)

(untitled) - Hazari, A.; Gouverneur, V.; Brown, J. M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Pigeon, X.; Bergeron, M.; Barabé, F.; Dubé, P.; Frost, H. N.; Paquin, J.-F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Paquin, J.-F. (Synlett, 2011)

(untitled) - Bergeron, M.; Johnson, T.; Paquin, J.-F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Bergeron, M.; Guyader, D.; Paquin, J.-F. (Org. Lett., 2012)

(untitled) - Champagne, P. A.; Pomarole, J.; Thérien, M.-È.; Benhassine, Y.; Beaulieu, S.; Legault, C. Y.; Paquin, J.-F. (Org. Lett., 2013)

(untitled) - Schneider, H.-J. (Chem. Sci., 2012)

(untitled) - Giuffredi, G. T.; Gouverneur, V.; Bernet, B. (Angew. Chem., Int. Ed., 2013)

(untitled) - Graton, J.; Wang, Z.; Brossard, A.-M.; Gonçalves Monteiro, D.; LeQuestel, J.-Y.; Linclau, B. (Angew. Chem., Int. Ed., 2012)

(untitled) - Scerba, M. T.; Leavitt, C. M.; Diener, M. E.; DeBlase, A. F.; Guasco, T. L.; Siegler, M. A.; Bair, N.; Johnson, M. A.; Lectka, T. (J. Org. Chem., 2011)

(untitled) - Bordwell, F. G.; Brannen, W. T. (J. Am. Chem. Soc., 1964)

(untitled) - Walsh, P. J.; Li, H.; Anaya de Parrodi, C. (Chem. Rev., 2007)

(untitled) - Kamlet, M. J.; Abboud, J. L. M.; Abraham, M. H.; Taft, R. W. (J. Org. Chem., 1983)